Overview of the application of open cell foam heat exchangers - S. A. Solovev; O. V. Soloveva; R. Z. Shakurova; Ya. P. Golubev (Известия высших учебных заведений: Проблемы энергетики, 2024)
PURPOSE. Review modern highly porous cellular heat exchangers.   METHODS. We conducted a broad literature review on highly porous cellular structures used as heat exchangers. We studied both domestic and foreign literature.   RESULTS. We analyzed highly porous heat exchangers of various structures: stochastic (foam with open and closed cells) and ordered (honeycombs and lattices). Methods for producing open/closed cell foams and additive technologies for producing honeycomb and lattice structures have been studied. The basic properties of highly porous structures are described. The factors influencing heat transfer and hydrodynamics in highly porous cellular heat exchangers are analyzed. A review of theapplication areas of highly porous metal heat exchangers is carried out.   CONCLUSION. Heat transfer and hydrodynamics in highly porous materials depend on structural parameters, such as porosity, cell size and geometry, diameter, and geometry of the strands. Increasing porosity and cell size leads to a decrease in heat transfer coefficient and pressure drop. Changing the cell geometry affects the specific surface area of the heat exchanger and the pressure drop. Cells with complex geometries, such as octet, have a large surface area and provide a high heat transfer coefficient but high resistance to coolant flow. Cells with simple geometries, such as a cube, on the other hand, provide low flow resistance and low heat transfer coefficient. In general, any structural parameter change affects heat transfer and hydrodynamics.